2021
DOI: 10.3390/jmse9020228
|View full text |Cite
|
Sign up to set email alerts
|

Mooring Analysis of a Floating OWC Wave Energy Converter

Abstract: This investigation focuses on the modelling of a floating oscillating water column (FOWC) wave energy converter with a numerical code (ANSYS AQWA) based on potential flow theory. Free-floating motions predicted by the numerical model were validated against experimental data extrapolated from a 1:36 scale model device in regular and irregular sea states. Upon validation, an assessment of the device’s motions when dynamically coupled with a four-line catenary mooring arrangement was conducted at different incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, to increase the threshold dynamicity extension and to include lengthier response periods in the SSE model, a former mechanism has been further upgraded, where it can select the range within [20,40,60,80] sec. It ought to be noted that for the model taut lashing, as comprehensively discussed in (Gubesch et al, 2021), the mooring system impacts the response characteristics substantially, in which higher exciting forces do not influence the response periods, but they affect response amplitudes. The moored nature also introduces many uncertainties in higher-order wave responses that cannot be quantified accurately.…”
Section: 3mentioning
confidence: 99%
“…Therefore, to increase the threshold dynamicity extension and to include lengthier response periods in the SSE model, a former mechanism has been further upgraded, where it can select the range within [20,40,60,80] sec. It ought to be noted that for the model taut lashing, as comprehensively discussed in (Gubesch et al, 2021), the mooring system impacts the response characteristics substantially, in which higher exciting forces do not influence the response periods, but they affect response amplitudes. The moored nature also introduces many uncertainties in higher-order wave responses that cannot be quantified accurately.…”
Section: 3mentioning
confidence: 99%
“…Recently, the hydrodynamic performance of a box-type moored OWC was studied numerically and experimentally. Specifically, in [189], the developed numerical modeling was compared against experimental data obtained from a test campaign in the wave basin with a 1:36 scale model. The study demonstrated that the wave direction significantly impacted sway, roll, and yaw motions while exerting a minimal effect on heave and pitch motions.…”
Section: Owc and Mooring Systemsmentioning
confidence: 99%
“…Theoretical studies play a crucial role in revealing hydrodynamic characteristics, primarily using linear water wave theory. The practicality and efficiency of the linearized approach have led to the continuous development of theoretical studies for OWC devices [54][55][56][57][58][59][60]. [24] investigated the behavior of the OWC device near an impermeable wall using the Galerkin technique (see Figure 6).…”
Section: Hydrodynamics Of Owcmentioning
confidence: 99%